Automated number plate recognition system for parking management - Norsailaniza Mohamad, 1994- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2017